Nutrition and epigenetics - Ho, Emily; Domann, Frederick (CRC Press Taylor & Francis Group, 2015)
"This book covers new information on the action of diet and nutritional determinants in regulating the epigenetic control of gene expression in health and disease. There are seven sections, and each section comprises a number of focused reviews on a given theme. This book is a resource to basic scientists and clinical researchers interested in nutrition, aging, and metabolic diseases." -- Provided by Publisher.